A chrmΘ number codes design. Issue 6 (1st November 2016) - Eteme, Fidele Ayissi
Abstract: At a fundamental level, number codes appear in microprocessor programming. More precisely in the computer's memory where they are used in programs written in computer languages: with hexadecimal address and binary contents, hexadecimal address and hexadecimal contents … The problem I pose may be outlined as follows. Design the chrm Θ number code in such a way that the following diagram be commutative: